RESEARCH ОF HYPERSPECTRAL RED EDGE INDІCES FOR VEGETATION COVER CHANGE DETECTION OVER THE OIL FIELD USING SPECTROMETRIC SURVEY DATA - Lyalko, V.I.; Shportiuk, Ƶ.M.; Sibirtseva, O.M.; Dugin, S.S. (Institute of Geological Sciences, NAS of Ukraine, 2014)
The variations of hyperspectral vegetation indices such as red edge position, MERIS terrestrial chlorophyll (TCI) and modified normalized difference vegetation index (NDVI705) using terrestrial cover spectrometry data over the Pryozerne oil field (Crimea) by the spectroradiometer FieldSpec® 3 FR to receive the searching indices are studied. As far as the points with the vegetation cover there are the limitation for NDVI705 ≥ 0.169 that distinguishes them from the other points in case of heterogeneous terrestrial cover. The lower magnitudes for all indices of interest relative to their background values out of field boundaries are observed for all points with vegetation cover over the oil field excepting the points near the oil boreholes. The strong correlation between REP and NDVI705 (r = 0.87) as well as TCI and NDVI705 (r = 0.88) and decreasing their values over the field shows the possibility of every index to respond to the changes of vegetation cover over hydrocarbon fields and give the informative index values in the prospecting goals only for the areas with the proper limitations of NDVI705.